ILC2s expanded by exogenous IL-33 regulate CD45+CD11b+F4/80high macrophage polarization to alleviate hepatic ischemia-reperfusion injury - Zhang, Hai-Ming; Chen, Xiao-Jie; Li, Shi-Peng; Zhang, Jin-Ming; Sun, Jie; Zhou, Liu-Xin; Zhou, Guang-Peng; Cui, Bin; Sun, Li-Ying; Zhu, Zhi-Jun (Frontiers in Immunology, 2022)
Hepatic ischemia-reperfusion injury (IRI) is an adverse consequence of hepatectomy or liver transplantation. Recently, immune mechanisms involved in hepatic IRI have attracted increased attention of investigators working in this area. In specific, group 2 innate lymphoid cells (ILC2s), have been strongly implicated in mediating type 2 inflammation. However, their immune mechanisms as involved with hepatic IRI remain unclear. Here, we reported that the population of ILC2s is increased with the development of hepatic IRI as shown in a mouse model in initial stage. Moreover, M2 type CD45+CD11b+F4/80high macrophages increased and reached maximal levels at 24 h followed by a significant elevation in IL-4 levels. We injected exogenous IL-33 into the tail vein of mice as a mean to stimulate ILC2s production. This stimulation of ILC2s resulted in a protective effect upon hepatic IRI along with an increase in M2 type CD45+CD11b+F4/80high macrophages. In contrast, depletion of ILC2s as achieved with use of an anti-CD90.2 antibody substantially abolished this protective effect of exogenous IL-33 and M2 type CD45+CD11b+F4/80high macrophage polarization in hepatic IRI. Therefore, this exogenous IL-33 induced potentiation of ILC2s appears to regulate the polarization of CD45+CD11b+F4/80high macrophages to alleviate IRI. Such findings provide the foundation for the development of new targets and strategies in the treatment of hepatic IRI.